Analysis of TaqMan Array Cards Data by an Assumption-Free Improvement of the maxRatio Algorithm Is More Accurate than the Cycle-Threshold Method. - Luigi Marongiu; Eric Shain; Lydia Drumright; Reidun Lillestøl; Donald Somasunderam; Martin D Curran (PLoS ONE)
Quantitative PCR diagnostic platforms are moving towards increased sample throughput, with instruments capable of carrying out thousands of reactions at once already in use. The need for a computational tool to reliably assist in the validation of the results is therefore compelling. In the present study, 328 residual clinical samples provided by the Public Health England at Addenbrooke's Hospital (Cambridge, UK) were processed by TaqMan Array Card assay, generating 15 744 reactions from 54 targets. The amplification data were analysed by the conventional cycle-threshold (CT) method and an improvement of the maxRatio (MR) algorithm developed to filter out the reactions with irregular amplification profiles. The reactions were also independently validated by three raters and a consensus was generated from their classification. The inter-rater agreement by Fleiss' kappa was 0.885; the agreement between either CT or MR with the raters gave Fleiss' kappa 0.884 and 0.902, respectively. Based on the consensus classification, the CT and MR methods achieved an assay accuracy of 0.979 and 0.987, respectively. These results suggested that the assumption-free MR algorithm was more reliable than the CT method, with clear advantages for the diagnostic settings.